Phytochelatin synthase activity as a marker of metal pollution - Zitka, Ondrej; Krystofova, Olga; Sobrova, Pavlina; Adam, Vojtech; Zehnalek, Josef; Beklova, Miroslava; Kizek, Rene (Journal of hazardous materials, 2011)
The synthesis of phytochelatins is catalyzed by γ-Glu-Cys dipeptidyl transpeptidase called phytochelatin synthase (PCS). Aim of this study was to suggest a new tool for determination of phytochelatin synthase activity in the tobacco BY-2 cells treated with different concentrations of the Cd(II). After the optimization steps, an experiment on BY-2 cells exposed to different concentrations of Cd(NO(3))(2) for 3 days was performed. At the end of the experiment, cells were harvested and homogenized. Reduced glutathione and cadmium (II) ions were added to the cell suspension supernatant. These mixtures were incubated at 35°C for 30min and analysed using high performance liquid chromatography coupled with electrochemical detector (HPLC-ED). The results revealed that PCS activity rises markedly with increasing concentration of cadmium (II) ions. The lowest concentration of the toxic metal ions caused almost three fold increase in PCS activity as compared to control samples. The activity of PCS (270fkat) in treated cells was more than seven times higher in comparison to control ones. K(m) for PCS was estimated as 2.3mM.
Keywords: aminoacyltransferasy; Aminoacyltransferases; Biomarkers; Environmental Pollutants; látky znečišťující životní prostředí; Cell Line; Chromatography, High Pressure Liquid; biologické markery; vysokoúčinná kapalinová chromatografie; buněčné linie; Metals; kovy